Pengembangan Lembar Kerja Peserta Didik Berbasis Inquiry Kelas X SMA Negeri 2 Gunungsitoli - Noveri Amal Jaya Harefa; Bertin Ayuning Putri Gea (Universitas Nias, 2023)
The problem with the learning process at SMA Negeri 2 Gunungsitoli is the lack of variation in the worksheets used so that students are less responsive and less motivated. This type of research is development research using the 4D model which consists of 4 stages, namely the definition stage, the design stage, the development stage, and the deployment stage. The results of this study are Inquiry-based Indonesian worksheets on material analyzing the meaning and language of biographical texts. Material expert assessment of revision I reached 78.7%, revision II reached 82.2%, linguist revision I reached 71.4%, revision II reached 82.1%, design expert revision I reached 78.3%, revision II reached 88.3% with very decent criteria. Based on the assessment of 86% individual trials, 90% small group trials and 93.8% field trials with very practical criteria. Assessment of student learning outcomes tests obtained a percentage of classical completeness in 100% individual trials, 100% small group trials and 83% field trials with very effective categories.